2012
DOI: 10.1007/s11284-012-0989-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal heterogeneity of water supply and nutrient levels on plant biomass growth depend on the plant's relative size within its population

Abstract: Temporal heterogeneity of water supply can alter the biomass growth of plants, even when the same total amount of water is provided. Most studies of heterogeneous watering have focused on responses of whole populations rather than individuals in a population. The effects of water supply heterogeneity may also depend on nutrient levels. Thus, we investigated the integrated effects of water supply heterogeneity and nutrient levels on plants within a population. Six plants of Perilla frutescens per pot were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Water supply is the one of the requirement for plant growth. It was confirmed that a stable water supply (homogeneity of water supply) can promote plant root systems to absorb water more efficiently and thus grow larger plants (Novoplansky and Goldberg, 2001;Hagiwara et al, 2012, Yu et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Water supply is the one of the requirement for plant growth. It was confirmed that a stable water supply (homogeneity of water supply) can promote plant root systems to absorb water more efficiently and thus grow larger plants (Novoplansky and Goldberg, 2001;Hagiwara et al, 2012, Yu et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Although many studies have tested effects of spatial patchiness or temporal heterogeneity in the supply of water on growth or clonal integration of plants 3 7 10 12 14 16 , none has examined the effects of both spatial and temporal heterogeneity in water supply. Our results obviously indicated that both spatial patchiness and temporal interval in water supply could partly alter growth and clonal integration of both species, especially for the invasive species H. vulgaris .…”
Section: Discussionmentioning
confidence: 99%
“…The proximal ramets might take up higher amounts of resources than distal ramets when exposed to such relatively high resource conditions (the homogeneous low interval in water) 27 . In the field, many natural habitats and some anthropogenic habitats are probably relatively homogeneous in space 29 and heterogeneous in time 7 10 , such as some shallow wetlands where water movement can homogenize fine-scale conditions. In consistent with a recently study in such relatively homogeneous water supply, the net effects of integration on clonal performance should be more positive at the high levels of spatially uniform water supply 26 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations